A D-type dual side-polished, highly sensitive, plasma refractive index sensor based on photonic crystal fiber - Zhang, Qinrong; Li, Wei; Ren, Qingyin; Zheng, Jiajin; Xie, Qiyun; Wang, Xiangfu (Frontiers in Physics, 2022)
In this paper, a D-shape dual side-polished (DSP) photonic crystal fiber (PCF) sensor based on high sensitivity and high range refractive index (RI) is proposed and analyzed. The surface of the structure is plated with Au and TiO2, which can enhance the surface plasmon resonance (SPR) effect and sensitivity. The characteristics of the sensor were analyzed by finite element method (FEM). Its RI scope of detection is 1.38–1.42, and by optimizing geometric parameters, the optimal wavelength sensitivity (WS) is 22,100 nm/RIU. Additionally, the WS for DSP-PCF is far better than the recently reported PCF sensors in the above mentioned RI detection range to the best of our knowledge. With these significant outcomes over the analyte RI range, which is helpful for the fields of environmental detection and medical diagnosis.